Multifocal Electroretinogram, Central Macula Thickness and Visual Acuity in Diabetic Macular Edema Following Intravitreal Injection of anti-VEGF - Nusanti, Syntia; Sampurna, Kirana; Djatikusumo, Ari; Yudantha, Anggun Rama; Prihartono, Joedo (International Journal of Retina, 2021)
Introduction : Diabetic Retinopathy (DR) is one of the major cause of visual acuity deterioration in diabetic patients. The loss of central visual acuity in diabetic patients are mainly due to macula edema, which is found in 29% diabetic patients with the over 20 years duration of disease. The aim of this study is to evaluate and investigate the possible correlation among changes of visual acuity (VA), central macular thickness (CMT) using Spectral Domain Optical Coherence Tomography (SD-OCT). Electrophysiological responses using multifocal electroretinography (MfERG) in diabetic macular edema (DME) following intravitreal injection of bevacizumab. Methods: Single arm clinical trial. Thirty-three eyes of 33 DME patients (16 non-proliferative diabetic retinopathy and 17 non-high-risk proliferative diabetic retinopathy), receives intravitreal bevacizumab 1,25mg. All patients underwent complete ophthalmic examination including ETDRS VA testing, Sixty-one scaled hexagon MfERG and SD-OCT scan at baseline, 1-week and 1-month post-injection. Components of the first order kernel (N1, N2 and P1) in central 2o were measured. Result : MfERG showed reduced P1 amplitude (P<0.05) at 1-week after injection followed by increased P1 amplitude (P>0.05) at 1-month after treatment as compared to the baseline in all subjects. There was 19% improvement CMT and 0.2Logmar VA improvement in 1-month post-injection compared to the baseline (P<005). This study showed no serious ocular adverse effects. There was no significant correlation between changes in visual acuity with changes in CMT or other MfERG parameters. Conclusion: Intravitreal injection bevacizumab resulting in improved VA, reduction in CMT and mild improvement in the MfERG responses. Although VA changes did not correlate with reduced CMT nor with improved responses of MfERG, the combined use of SD-OCT and MfERG may be used to evaluate macular function in DME patient with worsened visual acuity post anti-VEGF injection.